Reachability Matrix Ontology: A Cybersecurity Ontology. Issue 7 (7th June 2019) - Scarpato, Noemi; Cilia, Nicole Dalia; Romano, Marco
ABSTRACT: In this paper, we describe the Reachability Matrix Ontology (RMO). RMO aims to describe the networks and the cybersecurity domain in order to compute the reachability information (reachability matrix). Reachability Matrix determines if a node can reach another node (via ISO/OSI layers protocol). To achieve this objective RMO describes the network's elements, the network connectivity information, and the access control policies. RMO also provides some SWRL rules able to calculate the Reachability Matrix. Besides RMO and SWRL rules, there are also a set of SPARQL queries to refine the computation of the Reachability Matrix. To the best of our knowledge, RMO represents an innovative approach to the computation of the reachability matrix. Following we will describe our approach based on a strategy that exploits a combination of OWL, description logic rules and SPARQL queries.